O arsenal político-estético-pedagógico do teatro épico-dialético na práxis da Brava Companhia - Calló, Beatriz Georgopoulos [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
O teatro de grupo de São Paulo é responsável pela maior parte da produção teatral da cidade. Decorrente de processos de luta da categoria, esse sujeito histórico foi o grande ator social no que tange a descentralização e a democratização dos espetáculos de teatro. A partir dessa reunião de artistas e pensadores de teatro, é formulada e promulgada a Lei de Fomento ao Teatro Para a Cidade de São Paulo, que prevê a destinação de recursos públicos para a manutenção dos coletivos. Circunscrita nessa esfera está a Brava Companhia, grupo da periferia da Zona Sul da cidade de São Paulo, que realiza seu trabalho militante, transitando com os expedientes brechtianos, que estão presentes em grande parte da pesquisa estética dos grupos paulistanos. O trabalho analisa essa influência de Bertolt Brecht no trabalho da Companhia, tendo a peça Este lado para cima – isto não é um espetáculo como objeto dessa análise.

The group theater of Sao Paulo is responsible for most of the city's theatrical production. Due to the struggle processes of the category, this historical subject was the great social actor in what concerns the decentralization and democratization of theater plays. From this organization of artists and theater thinkers, the Law for the Promotion of Theater for the City of São Paulo, which implicates the destination of public resources for the maintenance of the collectives, is formulated and promulgated. Circumscribed in this sphere is the Brava Companhia, a group on the outskirts of the South Zone of the city of São Paulo, which carries out its militant work, transiting with the Brechtian expedients, which are present in most of the aesthetic research of the groups from Sao Paulo. The work analyzes this influence of Bertolt Brecht on the work of the Company, having the piece Este lado para cima – isto não é um espetáculo [This side up - this is not a spectacle] as object of this analysis.
The political-aesthetic-pedagogical arsenal of the epic-dialectic theater in the praxis of the Brava Companhia
Keywords: Brava Companhia; Bertolt Brecht; Arte contra a barbárie; Este lado para cima; Teatro de grupo de São Paulo; Expedientes épicos; Lei de fomento; Group theater of Sao Paulo; Brava Companhia; Bertolt Brecht; Epic expedients; Law of promotion of theater; Art against barbarism; Este lado para cima